THE ROLE OF CODE OF CONDUCT AT IMPROVING CHARACTER OF STUDENT’S CHARACTER IN SMPN 12 BANDUNG - Agustiani, Tia (Universitas Pendidikan Indonesia, 2018)
ABSTRACTThis research is motivated by concerns of authors to the implementation of the order in the SMP 12 Bandung. Of all the rules of conduct, the author wants to memfoskuskan on three chapters contained in the rules of conduct on the implementation of presence and neatness it is intended to look at the implementation of the rules on the implementation of the role and the presence of tidiness effect on increasing the students of SMPN 12 Bandung character class VIII- D. This study used descriptive qualitative approach. Data collected by interview and observation. The results of this study show that: First, an increase of 5 main characters of this value through the implementation of the rules at school by choosing the dimensions of presence and neatness, on the implementation of the order shows that school teaching and learning activities is not maximized. This happens due to lack of optimization of teachers in supporting the establishment of rules consistently; Second; Implementation presence in SMPN 12 Bandung views of punctuality when attending school, students attend school information, student activities conducted at the time of school hours attendance order dimension into forming values that must be owned by the students; Third, the neatness of this D class VIII in terms of appearance is shown in the environment of the school, from clothes, hair, accessories and footwear worn / shoes; Fourth.